A method for recycling positive electrode material and regeneration membrane thereof

By coarse crushing, heat treatment and fibrotic recombination of the positive electrode scraps in the dry film, a regenerated film with a performance comparable to the original positive electrode film was prepared, which solved the problem of difficult recycling and reusing of the scraps, and achieved efficient utilization of resources and reduced costs.

CN116259706BActive Publication Date: 2025-04-04BAOSHENG (SUZHOU)ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310269361.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-04-04
Estimated Expiration
2043-03-20

Smart Images

  • Figure CN116259706B_ABST
    Figure CN116259706B_ABST
Patent Text Reader

Abstract

The present invention provides a method for recycling and reusing positive electrode materials and a regenerated film thereof, which relates to the technical field of lithium ion battery materials, and comprises the steps of collecting the leftovers of positive electrode materials generated in the process of preparing the positive electrode film, crushing to obtain a coarse material; heating the coarse material to melt and recrystallize the binder fibers to obtain a heat-treated coarse material; then refining, fiberizing and reorganizing, and thinning and film-forming the obtained coarse film to obtain the final regenerated film. The method of the present invention is safe, non-toxic, and low in cost. It not only recycles and reuses the leftovers of the positive electrode materials of the battery, but also the quality of the prepared regenerated film is equivalent to the performance of the original positive electrode film, ensuring the consistency of the finished regenerated film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a method for recycling positive electrode materials and a regeneration membrane thereof. Background Art

[0002] With the promotion and application of electric vehicles, portable consumer electronics and the rapid development of large-scale energy storage, not only higher requirements are put forward for the energy density, capacity retention rate, cycle efficiency and tensile strength of batteries, but also the manufacturing cost of lithium-ion batteries needs to be further reduced. At the same time, the pollution problems generated in the manufacturing process also need to be solved urgently.

[0003] At present, the preparation of lithium-ion batteries mainly includes wet coating technology and dry electrode preparation technology. Among them, the wet coating technology forms a slurry by stirring and mixing dry powder with a binder containing a solvent, and continuously adding solvent to adjust the viscosity of the slurry. The slurry is coated on the current collector and dried to prepare the electrode. However, the wet coating technology has the following disadvantages: complex process, high environmental pollution, a large amount of toxic and harmful organic solvents are used in the preparation of the positive electrode slurry, and solid waste is difficult to recycle, which increases the cost; in recent years, dry film making technology has gradually received attention from the industry. This method avoids the use of any solvents when preparing lithium batteries, which can significantly simplify the manufacturing process and improve battery performance.

[0004] Chinese invention patent CN115275110A discloses a positive electrode dry film preparation process and a positive electrode dry film. The ternary positive electrode material, SP (conductive carbon black), and PTFE (polytetrafluoroethylene) are mixed and stirred to obtain a premix; the premix is ​​fiberized and baked to obtain a marshmallow-like mixture; then the mixture is mixed, folded repeatedly, and rolled multiple times to obtain a thicker film; finally, the thicker film is thinned to make a positive electrode dry film. The process is simple, reduces material waste, has low labor and material costs, and can improve production efficiency and production benefits.

[0005] Chinese invention patent CN114171710A discloses an in-situ preparation method of a dry electrode membrane and a dry electrode thereof. Under a dew point of -25--65°C, active material dry powder, polymer binder dry powder, and conductive agent dry powder are premixed, placed in an extruder and heated by radiation at 50-150°C to make the mixture in-situ crosslinked, and extruded to form a dry electrode membrane. The binder used in this method is a low-melting-point adhesive at 50-120°C. By using the dry electrode technology formed by the low-melting-point binder of the present invention, the thickness of the positive and negative electrode membranes is increased, that is, the active material load per unit area is increased, so the energy density is increased; the low-melting-point binder can form a uniform and well-contacted mixture with active material dry powders and conductive agent dry powders of different densities, which is beneficial to improving the battery cycle performance, capacity retention rate and cycle efficiency.

[0006] Although the electrode film has developed rapidly, according to statistics, the global demand for lithium battery positive electrode materials will increase from 470,000 tons in 2020 to 1.9 million tons in 2025. The domestic demand for lithium battery positive electrode materials is expected to reach 468,000 tons by 2025, with a demand of 347,000 tons for LFP (lithium iron phosphate) and 53,000 tons for LCO (lithium cobalt oxide). However, according to the technical data of wet coating in battery production, about 2% of the scraps of electrode coating and cutting processes will appear, and in dry film technology, the amount of this scrap will increase significantly, mainly from the multiple cutting edges in the step-by-step thinning process of the electrode film. The amount of this electrode scrap is huge. If it is reprocessed and utilized, the fiberization state of the electrode film after multiple hot pressing is completely different from the fiberization state of the initial material. Directly returning the material for film making without treatment can easily lead to uneven electrode film formation, thereby causing wrinkles, cracks and broken belts in the dry film. Therefore, for battery production and technological research, it is crucial to provide a method for preparing positive electrode materials with high capacity retention, high cycle efficiency and full and efficient utilization of positive electrode material scraps.

[0007] In view of this, in order to recycle and reuse the positive electrode scraps in the dry film making process, reduce the preparation cost of the dry electrode, and ensure the film quality of the dry electrode, it is urgent to develop a method for recycling and reusing the scraps in the preparation process. Summary of the invention

[0008] The present invention aims at the problems existing in the prior art and provides a method for recycling and reusing positive electrode materials and a regenerated film thereof. After recycling the positive electrode scraps in the dry film-making process, the scraps are crushed and heated to melt and recrystallize the binder fibers, and then fiberized and reorganized to form a coarse film. The coarse film is thinned and finally film-formed to prepare a regenerated film. The method not only recycles and reuses the scraps, but also the quality of the prepared regenerated film is equivalent to the performance of the original positive electrode film.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] In one aspect, the present invention provides a method for recycling anode materials, comprising the steps of:

[0011] S1, coarse crushing: collecting the leftovers of the positive electrode materials produced during the preparation of the positive electrode membrane and crushing them into coarse materials of 0.2-1.0 cm;

[0012] S2. Heat treatment: heating the coarse material to melt and recrystallize the binder fibers to obtain the heat-treated coarse material;

[0013] S3, sheeting: the heat-treated coarse material is smelted, fiberized and reorganized to obtain a coarse film with a thickness of 0.5-2.0 cm;

[0014] S4, film forming: the crude film is subjected to film forming treatment by a multi-roll thinning device to obtain a regenerated film.

[0015] In the present invention, the positive electrode material is a dry positive electrode film material in a dry electrode process.

[0016] In the present invention, the positive electrode material comprises components: an active material, a conductive material and a binder.

[0017] In the present invention, the active material in the positive electrode material is a lithium-containing compound that can be reversibly inserted and released.

[0018] Preferably, the active material in the positive electrode material is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based.

[0019] Further preferably, the active material in the positive electrode material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide.

[0020] In the present invention, the conductive material in the positive electrode material is selected from at least one of conductive carbon black, conductive graphite, acetylene black, carbon fiber VGCF, carbon nanotubes, and graphene.

[0021] In the present invention, in the positive electrode material, the binder used is selected from polytetrafluoroethylene (PTFE) and / or modified polytetrafluoroethylene.

[0022] Preferably, the mass ratio of the components in the positive electrode material is active material: conductive material: binder = 80-95: 3-15: 2-5.

[0023] Further preferably, the mass ratio of the components in the positive electrode material is active material: conductive material: binder = 82-90: 7-13: 3-5.

[0024] Preferably, in step S1, the crushing is selected from at least one of shear crushing, extrusion crushing, splitting crushing and impact crushing.

[0025] Further preferably, the crushing is shear crushing.

[0026] More preferably, the crushing is carried out in a crushing device for 0.5-2 hours, the shear speed is 100-300 r / min, and the d50 of the coarse material is 0.2-0.8 cm.

[0027] More preferably, the crushing is carried out in a crushing device for 1 hour, the shear speed is 200 r / min, and the d50 of the coarse material is 0.35-0.6 cm.

[0028] Preferably, in step S2, the heating temperature is 200-350°C, and the heating time is 0.5-3h.

[0029] More preferably, the heating temperature is 280-330° C. and the heating time is 1-2.5 h.

[0030] More preferably, the heating temperature is 300-330° C. and the heating time is 1-2 h.

[0031] In step S2 of the present invention, the heating process requires continuous stirring.

[0032] Preferably, in step S3, the temperature of the refining rollers is controlled at 150-280°C.

[0033] Further preferably, the temperature of the open mill rolls is controlled at 180-230°C.

[0034] More preferably, the temperature of the open mill rolls is controlled at 200°C.

[0035] Preferably, in step S3, the number of times of open refining is multiple times, more preferably 5-10 times.

[0036] Furthermore, the number of times of the open refining is 5-8 times.

[0037] Preferably, in step S3, the thickness of the crude film is 0.5-1 cm.

[0038] Preferably, in step S4, the thickness of the regenerated film is 70-200 um.

[0039] Preferably, the recycling and reuse method further comprises the step of carrying out the heat treatment in a dehumidification room with the dew point temperature controlled at -30-70°C.

[0040] Further preferably, the dew point temperature is controlled at -30--40°C.

[0041] In the present invention, the regenerated film can be rolled up for storage.

[0042] On the other hand, the present invention provides a regenerated membrane prepared by the recycling method.

[0043] In the present invention, the regenerated membrane is a positive electrode membrane.

[0044] In the present invention, the regeneration membrane includes components: an active material, a conductive material and a binder; the active material is a lithium-containing compound that can be reversibly embedded and released, and can be selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese base; the conductive material is selected from at least one of conductive carbon black, conductive graphite, acetylene black, carbon fiber VGCF, carbon nanotubes, and graphene; the binder is selected from polytetrafluoroethylene (PTFE) and / or modified polytetrafluoroethylene.

[0045] In the present invention, in the regenerated membrane, the mass ratio of the active material of the positive electrode material: the conductive material: the binder is 80-95: 3-15: 2-5.

[0046] In the present invention, the thickness of the regenerated membrane is 70-200um.

[0047] Preferably, the method for preparing the regenerated membrane comprises the steps of:

[0048] S1, coarse crushing: collecting the leftovers of the positive electrode materials produced during the preparation of the positive electrode membrane and crushing them into coarse materials of 0.2-1.0 cm;

[0049] S2. Heat treatment: heating the coarse material to melt and recrystallize the binder fibers to obtain the heat-treated coarse material;

[0050] S3, sheeting: the heat-treated coarse material is smelted, fiberized and reorganized to obtain a coarse film with a thickness of 0.5-2.0 cm;

[0051] S4, film forming: the crude film is subjected to film forming treatment by a multi-roll thinning device to obtain a regenerated film.

[0052] Further preferably, in step S2, the heat treatment temperature is 200-350°C, and the heat treatment time is 0.5-3h.

[0053] Further preferably, in step S3, the temperature of the refining rollers is controlled at 150-280°C.

[0054] Further preferably, after the heat treatment, steps S3 and S4 need to be performed in a dehumidification room, and the dew point temperature is controlled at -30-70°C.

[0055] Steps S3-S4, sheet discharging and film forming need to be carried out in a dehumidification room, and the dew point temperature is controlled at -30-40°C.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1. The present invention recycles and reuses the scraps generated during the dry process of preparing the positive electrode film, thereby achieving 100% utilization of the positive electrode active materials in the dry process, reducing the waste of lithium-containing positive electrode materials, greatly reducing the process cost of the dry process, and facilitating the promotion of the dry process.

[0058] 2. The present invention performs a certain degree of coarse crushing of the scraps, performs melting recrystallization at a certain heat treatment temperature and time, and adopts the principle of fiberization and recombination to recombine and bond the fiberized positive electrode membrane waste. The mechanical properties and electrochemical properties of the scrap-based regenerated positive electrode membrane and the original positive electrode membrane are almost the same. The recycling and reuse method of the present invention ensures the consistency of the regenerated positive electrode membrane product while recycling the waste.

[0059] 3. The recycling and reuse method adopted by the present invention is safe and non-toxic, low in cost, and is conducive to commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 The present invention provides a schematic flow chart of a method for recycling and reusing positive electrode materials;

[0061] Figure 2 This is a SEM image of the lithium iron phosphate positive electrode regeneration membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of protection claimed in this application, and those skilled in the art can make various changes and modifications to the invention of this application based on the disclosed content, which should also fall within the scope of protection claimed in this application.

[0063] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0064] In the following embodiment, a method for recycling positive electrode materials is described, and its process flow is as follows: Figure 1 shown.

[0065] Example 1

[0066] A method for recycling positive electrode materials comprises the following steps:

[0067] S1. Coarse crushing: Collect the trimming scraps of lithium iron phosphate dry cathode membrane a, whose components are lithium iron phosphate: conductive agent (conductive carbon black): PTFE binder = 85:10:5, put it into the shear crushing equipment through a conveyor belt and crush it for 1 hour. The shear speed is 200r / min to obtain a coarse material of 0.2-1.0cm, and d50 is about 0.6cm.

[0068] S2. Heat treatment: The coarse material obtained in S1 is put into a rotary furnace through a conveyor belt for heating to melt and recrystallize the binder fibers. The heating temperature is set to 330°C, the heating time is set to 1 hour, the speed of the rotary furnace is 5 r / min, and stirring is continuously performed during the heat treatment process to obtain the coarse material after heat treatment.

[0069] S3, sheeting: the coarse material after heat treatment in S2 is put into a fully automatic open mill with recyclable materials through a conveyor belt for fiberization and reorganization. The refining temperature is 200°C, and the roller gap of the open mill is fixed at 1 cm. After 5 times of refining and refining, a coarse film with a thickness of 1 cm is obtained after sheeting.

[0070] S4, film forming: the rough film obtained in S3 is thinned by a three-roll thinning machine, and different roller gap parameters are set to obtain lithium iron phosphate positive electrode regeneration films b of 70 um, 100 um and 150 um respectively, and then rolled up for storage.

[0071] Steps S3 and S4 were performed in a dehumidification room with a dew point temperature of -40°C.

[0072] The lithium iron phosphate positive electrode regeneration membrane b prepared in this embodiment was subjected to SEM testing to observe the fibrosis of its PTFE. The SEM image is shown in Figure 2 .

[0073] In order to verify the reliability of the lithium iron phosphate positive electrode regeneration membrane, the performance of the lithium iron phosphate dry positive electrode membrane a and the lithium iron phosphate positive electrode regeneration membrane b from the same batch were tested and compared. The test results are shown in Tables 1 and 2.

[0074] Example 2

[0075] A method for recycling positive electrode materials comprises the following steps:

[0076] S1. Coarse crushing: Collect the trimming scraps of the dry-process positive electrode membrane c of nickel cobalt lithium manganese oxide, whose components are nickel cobalt lithium manganese oxide: conductive agent (carbon nanotubes): PTFE binder = 90:7:3, and put it into the shear crushing equipment through a conveyor belt for crushing for 1 hour. The shear speed is 200r / min to obtain a coarse material of 0.2-0.5cm, and d50 is about 0.35cm.

[0077] S2. Heat treatment: The coarse material obtained in S1 is put into a rotary furnace through a conveyor belt for heating to melt and recrystallize the binder fibers. The heating temperature is set to 300°C, the heating time is set to 2h, the speed of the rotary furnace is 5r / min, and stirring is continuously performed during the heat treatment process to obtain the coarse material after heat treatment.

[0078] S3, sheeting: the coarse material after heat treatment in S2 is put into a fully automatic open mill with recyclable materials through a conveyor belt for fiberization and reorganization. The refining temperature is 200°C, and the roller gap of the open mill is fixed at 0.5 cm. After 8 times of recycle, the refining is repeated to produce sheets, and a coarse film with a thickness of 0.5 cm is obtained after sheeting.

[0079] S4, film forming: the rough film obtained in S3 is thinned by a three-roll thinning machine, and different roller gap parameters are set to obtain 70um, 100um and 150um nickel cobalt manganese oxide lithium positive electrode regeneration films d, which are rolled up and stored.

[0080] Steps S3 and S4 were performed in a dehumidification room with a dew point temperature of -40°C.

[0081] Example 3

[0082] A method for recycling positive electrode materials comprises the following steps:

[0083] S1. Coarse crushing: Collect the trimming scraps of lithium manganese iron phosphate dry-process positive electrode membrane f, whose components are lithium manganese iron phosphate: conductive agent (conductive carbon black): PTFE binder = 82:13:5, and put it into the shear crushing equipment through a conveyor belt for crushing for 1 hour. The shear speed is 200r / min to obtain a coarse material of 0.2-1.0cm, and d50 is about 0.6cm.

[0084] S2. Heat treatment: The coarse material obtained in S1 is put into a rotary furnace through a conveyor belt for heating to melt and recrystallize the binder fibers. The heating temperature is set to 300°C, the heating time is set to 2h, the speed of the rotary furnace is 5r / min, and stirring is continuously performed during the heat treatment process to obtain the coarse material after heat treatment.

[0085] S3, sheeting: the coarse material after heat treatment in S2 is put into a fully automatic open mill with recyclable materials through a conveyor belt for fiberization and reorganization. The refining temperature is 200°C, and the roller gap of the open mill is fixed at 1 cm. After 8 times of refining and refining, a coarse film with a thickness of 1 cm is obtained after sheeting.

[0086] S4, film forming: the rough film obtained in S3 is thinned by a three-roll thinning machine, different roller gap parameters are set to obtain 70um, 100um and 150um lithium manganese iron phosphate positive electrode regeneration films g, and the films are rolled up for storage.

[0087] Steps S3 and S4 were performed in a dehumidification room with a dew point temperature of -40°C.

[0088] Comparative Example 1

[0089] In order to verify the effectiveness and advancement of the recycling and reuse method of the present invention, Comparative Example 1 was set up.

[0090] Different from Example 2, in step S1, the trimming scraps of the nickel cobalt manganese oxide dry positive electrode membrane c are finely crushed until the particle size is consistent with the dry powder particle size of the original positive electrode material (the particle size is about 5um), and the dry powder of the original positive electrode material is mixed in a 1:1 ratio to prepare the dry membrane, that is, the dry raw material mixed with the scrap powder is used to press the positive electrode membrane using the original dry process flow, and the obtained positive electrode membrane e is retained as a control sample.

[0091] The original dry process flow is specifically as follows: the dry powder is put into a fully automatic open mill with recyclable materials through a conveyor belt for fiberization and reorganization, the refining temperature is 200°C, the roller gap of the open mill is fixed at 0.5 cm, and the sheet is produced after 8 rounds of recycle. After the sheet is produced, a rough film with a thickness of 0.5 cm is obtained; the obtained rough film is thinned by a three-roll thinning machine, and different roller gap parameters are set to obtain 70um, 100um and 150um nickel cobalt manganese oxide lithium positive electrode films, which are then rolled up for storage.

[0092] In order to verify the reliability of the nickel cobalt manganese oxide positive electrode regeneration membrane, the nickel cobalt manganese oxide dry positive electrode membrane c, nickel cobalt manganese oxide positive electrode regeneration membrane d and control group positive electrode membrane e from the same batch were tested for performance comparison. The test results are shown in Tables 1 and 2.

[0093] Comparative Example 2

[0094] In order to verify the necessity of the melt-recrystallization process, Comparative Example 2 was set up.

[0095] The difference from Example 3 is that in step S2, the heating temperature of the heat treatment is set to 120° C. and the heating time is set to 2 h. The remaining steps and parameters are the same as those of Example 3. A positive electrode film h is obtained.

[0096] Comparative Example 3

[0097] In order to verify the necessity of the melt-recrystallization process, Comparative Example 3 was set up.

[0098] The difference from Example 3 is that the heat treatment fiberization and reorganization step S2 is omitted, and the coarse material is directly smelted into sheets. The remaining steps and parameters are the same as those of Example 3. A positive electrode membrane i is obtained.

[0099] Comparative Example 4

[0100] Different from Example 3, in step S1, the size of the coarse material obtained by the crushing is 0.02-0.1 cm, and d50 is about 0.06 cm.

[0101] The remaining steps and parameters are the same as those in Example 3. A positive electrode film j is obtained.

[0102] Comparative Example 5

[0103] The difference from Example 3 is that in step S3, the temperature of the open mill rolls is set to 100°C.

[0104] The remaining steps and parameters are the same as those in Example 3. A positive electrode film k is obtained.

[0105] Comparative test 1SEM detection

[0106] The SEM image of the lithium iron phosphate positive electrode regeneration membrane of Example 1 is as follows: Figure 2 As shown, it can be seen that the PTFE fiberization of the obtained regenerated membrane is uniform and orderly, the PTFE fiber diameter is in line with the normal situation, and it is in a uniform and tight bonding state with the lithium iron phosphate particles.

[0107] Comparative test 2 Mechanical properties - tensile strength test

[0108] 1. Testing method: A mechanical tensile test was performed on all embodiments and comparative examples, as well as the original dry-process positive electrode membrane.

[0109] According to the method specified in GB / T 13022-1991, it is measured using a universal mechanical testing machine.

[0110] 2. Test results: The experimental results of tensile strength (MPa) are shown in Table 1 below:

[0111] Table 1

[0112] Tensile strength / MPa 70um 100um 150um Example 1, a 4.86 5.23 5.86 Example 1, b 4.92 5.53 5.98 Example 2, c 3.67 4.01 4.23 Example 2, d 3.73 4.12 4.38 Comparative Example 1, e 1.86 2.55 2.98 Example 3, f 4.68 4.91 5.53 Example 3, g 4.91 5.12 5.68 Comparative Example 2, h / 3.03 3.62 Comparative Example 3, i / / 2.92 Comparative Example 4, j / 3.97 4.25 Comparative Example 5, k / 2.91 3.15

[0113] It can be seen from Example 1 in Table 1 that the mechanical properties of the regenerated membrane b are good, and the tensile strength is comparable to that of the dry membrane a of the same batch. Figure 1 This indicates that after melt recrystallization and fiberization reorganization, the PTFE fiber can reach or approach the fiber network structure of PTFE after dry fibrillation.

[0114] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the mechanical properties of regenerated membrane d are good, and the tensile strength is equivalent to that of the dry membrane c from the same batch, while the mechanical properties of the positive electrode membrane e in the control group are poor. In actual experience, the positive electrode membrane obtained by the control group process is prone to wrinkles, cracks and broken belts, which is not suitable for large-scale production. It can be seen from Example 3 and Comparative Examples 2-3 in Table 1 that the mechanical properties of regenerated membrane g are good, and the tensile strength is equivalent to that of the dry membrane f from the same batch; while the mechanical properties of the control group h membrane under 120°C heat treatment are general, and the tensile strength of the unheat-treated i membrane is poor, and the film-forming effect is not good, indicating the importance of heat treatment to the melt recrystallization of PTFE fibers, and that there are certain requirements for the range of heat treatment melting temperatures.

[0115] It can be seen from Example 3 and Comparative Example 4 in Table 1 that the particle size of the coarse material obtained by crushing will affect the processability of the regenerated film. When the particle size is not within the range described in the present application, the tensile strength of the regenerated film is significantly reduced, and when pressed to a thinner thickness, it no longer has mechanical stretchability.

[0116] It can be seen from Example 3 and Comparative Example 5 in Table 1 that when the refining temperature is not within the range described in the present application, the mechanical strength of the obtained regenerated membrane is poor. The reason is that the softening temperature of the corresponding binder during fiberization and reorganization has a certain range.

[0117] Comparative test 3: electrical performance test

[0118] 1. Testing method: For all embodiments and comparative examples, as well as the original dry-process positive electrode membrane, a 100 um membrane was selected and composited with an aluminum foil current collector to test the electrochemical performance.

[0119] The dry-process positive electrode sheet after the composite current collector and the commercial graphite negative electrode, separator and electrolyte were assembled into a soft-pack battery, and the electrochemical performance was tested. In an environment of 25°C, the lithium-ion battery was charged and discharged for the first time, and constant current charging was performed at a charging current of 1C until the upper limit voltage was reached and constant voltage charging was switched, and then constant current discharge was performed at a discharge current of 1C until the final voltage was 3V, and the charge and discharge capacity of the first cycle was recorded and the first week efficiency was calculated; then 100 charge and discharge cycles were performed, and the cycle retention rate of 100 cycles was calculated.

[0120] 2. Test results: The electrochemical performance test results are shown in Table 2.

[0121] Table 2

[0122]

[0123]

[0124] As can be seen from Table 2, in Example 1, the electrochemical performance of the regenerated membrane b is very close to that of the dry-process cathode membrane a of the same batch, indicating that the regenerated membrane and the original dry-process cathode membrane have high electrochemical consistency and can be used equally.

[0125] It can be seen from Table 2 that the electrochemical performance of the regenerated membrane d in Example 2 is very close to that of the dry-process positive electrode membrane of the same batch, indicating that the regenerated membrane and the original dry-process positive electrode membrane have high electrochemical consistency and can be used equally; while the electrochemical performance of the positive electrode membrane e in Comparative Example 1 is unqualified.

[0126] It can be seen from Table 2 that the regenerated membrane in Example 3 maintains the electrochemical performance of the original dry-process positive electrode membrane, and exhibits a relatively high level in terms of capacity, first efficiency and cycle.

[0127] As can be seen from Table 2, it can be seen from Example 3 and Comparative Example 2 that when the heat treatment temperature is lower than the melting recrystallization temperature of the binder, the electrochemical performance of the resulting regenerated membrane is poor, which is manifested in the attenuation of the cycle capacity due to the polarization of the electrode.

[0128] The positive electrode film prepared by the preparation method of Comparative Example 3 has poor mechanical properties, and it is difficult to prepare a reliable electrode for electrochemical performance testing.

[0129] As can be seen from Table 2, in Example 3 and Comparative Examples 4 and 5, when the coarse material particle size and the refining temperature are not within the range given in this application, the electrochemical performance of the obtained regenerated membrane is far worse than that of the original dry electrode membrane, and the consistency is unqualified and therefore cannot be mixed.

[0130] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for recycling positive electrode materials, characterized in that: Includes steps: S1, coarse crushing: collecting the leftovers of the positive electrode materials produced in the process of preparing the positive electrode membrane, and crushing them into coarse materials of 0.2-1.0 cm; the positive electrode material is the dry positive electrode membrane material in the dry electrode process; the d50 of the coarse materials is 0.2-0.8 cm; S2. Heat treatment: heating the coarse material to melt and recrystallize the binder fibers to obtain a heat-treated coarse material; the heating temperature is 200-350° C. and the heating time is 0.5-3 hours; S3, sheeting: the heat-treated coarse material is subjected to open refining, fiberization and reorganization to obtain a coarse film with a thickness of 0.5-2.0 cm; the temperature of the open refining roller is controlled at 150-280° C., and the number of open refining is multiple; S4, film forming: the crude film is subjected to film forming treatment by a multi-roll thinning device to obtain a regenerated film.

2. The recycling method according to claim 1, characterized in that: The positive electrode material comprises components: an active material, a conductive material and a binder; the active material in the positive electrode material is a lithium-containing compound that can be reversibly inserted and removed.

3. The recycling method according to claim 2, characterized in that: The active material is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based.

4. The recycling method according to claim 2, characterized in that: The conductive material is selected from at least one of conductive carbon black, conductive graphite, carbon fiber VGCF, carbon nanotubes, and graphene; the binder is selected from polytetrafluoroethylene and / or modified polytetrafluoroethylene.

5. The recycling method according to claim 2, characterized in that: The mass ratio of each component in the positive electrode material is active material: conductive material: binder = 80-95: 3-15: 2-5.

6. The recycling method according to claim 1, characterized in that: In step S3, the number of times of refining is 5-10 times.

7. The regenerated membrane prepared by the recycling method according to any one of claims 1 to 6.

8. The regenerated membrane according to claim 7, characterized in that: The regeneration membrane comprises components: an active material, a conductive material and a binder; the active material is a lithium-containing compound that can be reversibly embedded and released, and is selected from at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese base; the conductive material is selected from at least one of conductive carbon black, conductive graphite, carbon fiber VGCF, carbon nanotubes, and graphene; the binder is selected from polytetrafluoroethylene and / or modified polytetrafluoroethylene; The thickness of the regenerated membrane is 70-200um.

Citation Information

Patent Citations

  • In-situ preparation method of dry-method electrode membrane and dry-method electrode thereof

    CN114171710A

  • Positive electrode dry-method film forming preparation process and positive electrode dry-method diaphragm

    CN115275110A

  • High-performance positive electrode material regenerated by simple solid-phase recovery method and preparation method thereof

    CN112777648A

  • Method for monitoring fibrosis degree in dry-method membrane preparation process, dry-method membrane preparation method, and preparation method and application of dry-method electrode plate

    CN114441408A